2017
DOI: 10.1007/s11306-017-1292-x
|View full text |Cite|
|
Sign up to set email alerts
|

Exploration of serum biomarkers for predicting the response to Inchinkoto (ICKT), a Japanese traditional herbal medicine

Abstract: IntroductionIn patients with obstructive jaundice, biliary drainage sometimes fails to result in improvement. A pharmaceutical-grade choleretic herbal medicine, Inchinkoto (ICKT), has been proposed to exert auxiliary effects on biliary drainage; however, its effects are variable among patients.ObjectivesThe aim of this study is to explore serum biomarkers that are associated with pharmaceutical efficacy of ICKT.MethodsObstructive jaundice patients who underwent external biliary decompression were enrolled (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
5
9
0
Order By: Relevance
“…Significant correlations between the levels of ICKT components (e.g., geniposide, dimethylesculetin, and conjugated genipin) in the serum on days 1 and 4 and changes in hepatobiliary markers were not observed. This finding was consistent with those of a previous study (Uji et al, 2017).…”
Section: Correlation Analysissupporting
confidence: 94%
See 3 more Smart Citations
“…Significant correlations between the levels of ICKT components (e.g., geniposide, dimethylesculetin, and conjugated genipin) in the serum on days 1 and 4 and changes in hepatobiliary markers were not observed. This finding was consistent with those of a previous study (Uji et al, 2017).…”
Section: Correlation Analysissupporting
confidence: 94%
“…Pearson correlation analysis was performed to explore relationships among the serum endogenous metabolites, ICKT components, and hepatobiliary markers. A previous study reported that the serum total bilirubin was closely correlated with several serum metabolites (Uji et al, 2017). The present study also demonstrated that the levels of 20-carboxyarachidonic acid and cystathionine were closely correlated with those of serum total bilirubin on days 1 and 4 (Fig.…”
Section: Correlation Analysissupporting
confidence: 84%
See 2 more Smart Citations
“…GC/MS was carried out using GCMS-TQ8040 (Shimadzu Co., Kyoto, Japan) with a DB-5 capillary column (30 m × 0.25 mm i.d. ; 1 μm film thickness; Agilent J & W Scientific, Folsom, CA, USA) as described previously [ 26 ]. The inlet temperature was set at 250 °C, and the injection volume was 1 μL (splitless mode).…”
Section: Methodsmentioning
confidence: 99%